Commensal Bacteria: Not Just Innocent Bystanders - Michael A. Apicella (mBio, 2019)
ABSTRACT Neisseria gonorrhoeae is quickly becoming untreatable due to its acquisition of resistance to multiple antimicrobials. It is vital that we begin to understand the mechanisms by which this is occurring. The paper by C. E. Rouquette-Loughlin, J. L. Reimche, J. T. Balthazar, V. Dhulipala, et al. (mBio 9:e02281-18, https://doi.org/10.1128/mBio.02281-18) has shown that horizontal transfer of DNA from a nasopharyngeal commensal, Neisseria polysaccharea, has resulted in multiple sequence changes in the mtr locus that affect both regulatory and structural regions of the MtrCDE pump, resulting in low-level azithromycin resistance. Studies such as this are increasingly important in our understanding of the movement of resistance between species and for devising strategies to overcome such events.